1999
DOI: 10.1352/0895-8017(1999)104<0270:rofeef>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Facial Emotional Expressions From Moving and Static Displays by Individuals with Mental Retardation

Abstract: Moving and static videotaped and photographic displays of posed emotional expressions were presented to 12 adults with mental retardation and 12 without mental retardation to investigate the role of movement in the recognition of facial expressions of emotion. Participants chose the corresponding emotion portrayed by the displays from among six written and pictorial labels of the emotions. Results indicated that individuals with mental retardation were significantly poorer at identifying anger, fear, disgust, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 0 publications
4
60
3
1
Order By: Relevance
“…In studies with typically developing persons, better performance on emotion recognition tasks was found when dynamic faces were used, in comparison with static faces (Harwood, Hall, & Shinkfield, 1999;Wehrle, Kaiser, Schmidt, & Scherer, 2000). Similar findings were obtained with individuals with ASD (Back et al, 2007).…”
supporting
confidence: 65%
“…In studies with typically developing persons, better performance on emotion recognition tasks was found when dynamic faces were used, in comparison with static faces (Harwood, Hall, & Shinkfield, 1999;Wehrle, Kaiser, Schmidt, & Scherer, 2000). Similar findings were obtained with individuals with ASD (Back et al, 2007).…”
supporting
confidence: 65%
“…Identification studies in which few distracters and static but ecologically valid stimuli were used showed no performance differences between participants with mental retardation and typically developing children of equivalent mental ages [1], though investigators employing identification tasks with more distracters or ambiguous stimuli found relative performance deficits [10,11]. In the present study subjects with mental retardation perform less well than normal children on subtle pictures and comics because they may not be confident in their own abilities to understand a stimulus that does not contain cues they have previously experienced.…”
Section: Discussioncontrasting
confidence: 60%
“…Q̳̯ῢῌ ̮Q̮̰ῡ QῒQῠ̮ῗ̰Q̮ῡῷQ̰QQ̰῍ Q̰̮QΊ῝̳ῡQ̮ῠῢῌ 2 ̯ῡ Q῟̮̰῍ QQ̳̮̰QQ̮QQῡ̮Qῤ̯ῡQQ Q̯ῘῸ̯QQῘῸ̰̳ῦQQΰQQῙ̯̰῍ 60 ῞ῡQQQῺQῢῌ 3 ̯ῡ`Ύῳῡ̮QQQ̰QQῚ̰῝῍ Q̲ῢQQΰQQῙῡῥ̰̳Ὺ̯̮̰ῌ Q Q̲ῢQQ̮QQῡ̮Q̯QQῚ̰῝῍ Q̰Q̮̲ῢῌ QQ̳̯QQ̮QQῡ̮QῡQQ̲̯QQῚ̰̯ ῝῍ Ῐ̰̰ῡ̮QQQῢῌ QQQ Qῠ̳̯῝ 8 Q ῑ̮̮Ί῝ῌ ̮̰Ίῌ ῡῪΰ̰Ί῝ῌ Q ῝ῌ ῝ῌ Q̰Ίῌ Q῟῝ῌ ̮Ίῒ ̯QQῚ̰̯῝῍ QQQῺQῢῌ ̮QQQ̰ A#ect Grid (Russell, Weiss, & Mendelsohn, 1989)ῌ ̳QQQΊῌ ̱ῬῐΊ (Likert, 1932) (Harwood, Hall, & Shinkfield, 1999;Lemay, Kirouac, & Lacouture, 1995; ῟ ̯ ῟ ̯ ῒQQῠ Q̳ Q 5 Q 1 Q 2 0 0 7 ΐῌ 53ῌ61 (Harwood et al, 1999;Humphrey, Donnelly, & Riddoch, 1993)῍ Ί̱ῲῩQQ̰ῌ QῩ̳̮̱Q Q ῲ Ῠ ̯ ̮̱ῶ´Ὸ ῏Ί (e. g., Ekman, 1972) ῩQῒῨQῡ΅ῩῥQ̮ῲ̱̱῍ ̳̳ῤῌ ΅̮ 1 ῡῩ ̲Q῾̲ ῥ῝ΰQQΊῖ̯Q῞̱ (e.g., Russell & Bullock, 1985)῍ ΊῩQῒῤ̰ῌ ̮ῲ ̱ ̰Qῌ Qῌ Q̮ῌ Q̮ῥ̮ῠ̯Q QQQ ῤQ̮̱̯QQῼῩQ̱̮Ῡ ̰Ῠ ̰̱̱ῥ῝ῌ (Russell, Weiss, & Mendelsohn, 1989) Ῡ̮Ῠ ̱Q QQQῑῨ῭Ῑ Q῝̯ῳῌ ῼ ῶ῏̲Q (Likert, 1932 ῍ ̯ῥQ̲ῌ ῑQ ̮ῒῌ ῑQ῟̮ῒῌ ῑ̮Ῑ̮Ῑ῟̯ῒ QQῤῖ̮ῠQQ̲Ῐ Qῶῡ̮̯̯ (Fs(2, 118)3.37, ps.05)῍ QQQ΅ Q̯̯Q̲ῌ ῑQ̮ῒ ῖ̰ῧ ῑQ῟̮ῒ QQῡῦῌ Q̲ ῥQQQQῦQῪQ̮̲̰Ὺ̰QῶῤQῚῌ ῑ̮Ῑ̮Ῑ ῟̯ῒQQῡῦῌQQ̲ῥQQQQῦQῪQ̮̲̰Ὺ̰Q ῶῤQῗ̯̯῍ ῐ῎῍ῌ῏ῑ ̱ῳ῎̱Qῗ̰Q̰Ῥ̯̱῎ῲῤ̯ ̮ῠQQQQ̲ῤQ῟̯QQ΅Q̮̯̰ῤῌ ῾QQῤQ ̯Ύ 8 ̯ῥ QQῥQQQῤ̯̮ῠQQQQQ΅Q̯ ̯῍ QQQ̳ῡῦQQ΅ ̰̯ Q̳ ΅ 2 QQῡῢ ̰̮Ύ̰ῥῘQ̮ (Russell & Bullock, 1985;Katsikitis, 1997) ῢ΅ῗ`Ῐ̰ῌ Q 2 QQQῩῡQQ῟̯῍ ῌQQQQῦ 54.5̮ῡ̮̯̯῍ QQQQQῥQ̲΅ Table 3 ῤQ̯῍ Table 3 ̰Ὺῌ Q 1 QQQῡῦ ῑ̮Ῥ ῟̮ῒῌ ῑῥ`ῧῪ῟̯ῒῌ ῑ̮Ῑ̮Ῑ῟̯ῒ ῘQῤQ̲῟ῌ ῑ̳῭῟̮ῒῌ ῑQ῟̮ῒῌ ῑQ̯̯ῒ ῘQῤQ̲῟ῠ̮Ύ ῢῗ̰ῌ Q 1 QQQῦῌ ῏̲ῌQ̲ῐ ΅Q̯QQῤQ Q̯ΎῢQ̮̰ῬΎ῍ Ῡ̯ῌ Q 2 QQQῡῦῌ ῑ̮Ῑ̮ Ῑ῟̯ῒῌ ῑ̳̮̯ῒῌ ῑ̳῭῟̮ῒ ῘQῤQ̲῟ῌ ῑQ̮ῒῌ ῑῥ`ῧῪ῟̯ῒῌ ῑQ῟̮ῒ ῘQῤQ̲῟ῠ̮Ύῢῗ ̰ῌ Q 2 QQQῦῌ ῏ QῌQ Qῐ ΅Q̯QQῤQQ̯ ΎῢQ̮̰ῬΎ῍ ῾QQῥQQQQQῤ̯̮ῠQQῖ̰ῧQQQQ῝ῢ ῥQ̳Q΅ῌ Q 1 QQQ΅ῼQῤῌ Q 2 QQQ΅QQ ῤQ῟̯ 2 QQ̳ QῤQQ῟̯̰ῥ΅ Figure 3 ῤQ ̯῍ Q̲ῌ QQ̲ῌ QῪQ̮̲ῢ̰ῤῌ ῑQ̮ῒ QQῘ ̰̰QῬῠQQ῞Ῥῠ̮Ύ̰ῥῥQQQ῍ῦ QῥῺ ̱̱ῴ (e.g., Russell & Bullock, 1985) …”
mentioning
confidence: 99%